Myxoid liposarcoma: a rare soft tissue tumour in the breast - Abdullah, Maizaton Atmadini; Mat Sain, Abdul Hamid; Abd. Ghani, Fauzah (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2020)
Liposarcoma is one of the most common mesenchymal tumour in adults but it is rare to occur in the breast. Our case was a 50 year old single nulliparous woman who presented with a right breast mass for one year duration. The mass was progressively increasing in size in the last few months. Breast examination showed a huge mass measuring 5 x 8 x 6 cm occupying the entire right breast. Mammogram showed a large homogenous soft tissue mass occupying the entire right breast with foci of calcification. A trucut biopsy showed a cellular tumour which was thought to be an invasive carcinoma. The patient underwent right modified radical mastectomy with axillary clearance. Macroscopy showed a well circumscribed lobulated solid haemorrhagic yellowish tumour mass measuring 180 x 110 x 50 mm. Microscopically the tumour was heterogenous comprising cellular round nonlipogenic mesenchymal cells and loose myxoid areas containing small cells. The typical arborizing ‘chicken wire’ capillaries were observed. Vacuolated lipoblasts were seen. All eleven axillary lymph nodes sampled showed no metastasis. A diagnosis of a myxoid liposarcoma was made. To raise the suspicion of a possible mesenchymal tumour, it is very important for clinicians to relay the clinical and radiological findings to the pathologist to avoid misdiagnosis in a trucut biopsy.